Multi-cycle operation of enhanced biological phosphorus removal (EBPR) with different carbon sources under high temperature - Shen, Nan (2017)
Many studies reported that it is challenging to apply enhanced biological phosphorus removal (EBPR) process at high temperature. Glycogen accumulating organisms (GAOs) could easily gain their dominance over poly-phosphate accumulating organisms (PAOs) when the operating temperature was in the range of 25 °C–30 °C. However, a few successful EBPR processes operated at high temperature have been reported recently. This study aimed to have an in-depth understanding on the impact of feeding strategy and carbon source types on EBPR performance in tropical climate. P-removal performance of two EBPR systems was monitored through tracking effluent quality and cyclic studies. The results confirmed that EBPR was successfully obtained and maintained at high temperature with a multi-cycle strategy. More stable performance was observed with acetate as the sole carbon source compared to propionate. Stoichiometric ratios of phosphorus and carbon transformation during both anaerobic and aerobic phases were higher at high temperature than low temperature (20±1 °C) except anaerobic PHA/C ratios within most of the sub-cycles. Furthermore, the fractions of PHA and glycogen in biomass were lower compared with one-cycle pulse feed operation. The microbial community structure was more stable in acetate-fed sequencing batch reactor (C2-SBR) than that in propionate-fed reactor (C3-SBR). Accumulibacter Clade IIC was found to be highly abundant in both reactors.